Popular nationalism: Global Times and the US–China trade war. (February 2020) - Zeng, Wenna; Sparks, Colin
This article analyses the coverage of the current US–China trade war in the Global Times . Some scholars argue that official nationalism, which stress the unity of the Chinese people, is challenged by popular nationalism, which privileges the dominant Han ethnicity, and that official nationalism is forced to make concessions to popular nationalism. If this is true, then one would expect to find evidence in the coverage of international issues in a 'popular' official newspaper like Global Times . The newspaper's coverage stresses negative features of the USA, but devotes considerable space to the damage that Trump's policies are doing to ordinary Americans. It does not present China as the unique victim of US economic aggression. The coverage stresses broad international agreement for free trade, leaving the USA isolated in adopting protectionist policies. At least in this instance, state-led nationalism remains central and no concessions are made to popular sentiments.